2010
DOI: 10.1189/jlb.0710395
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage motility requires distinct α5β1/FAK and α4β1/paxillin signaling events

Abstract: Macrophages function as key inflammatory mediators at sites of infection and tissue damage. Integrin and growth factor receptors facilitate recruitment of monocytes/macrophages to sites of inflammation in response to numerous extracellular stimuli. We have shown recently that FAK plays a role in regulating macrophage chemotaxis and invasion. As FAK is an established downstream mediator of integrin signaling, we sought to define the molecular circuitry involving FAK and the predominant β1 integrin heterodimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 35 publications
(58 reference statements)
2
38
0
Order By: Relevance
“…19 Moreover, later evidences definitively linked FAK to macrophage migration. 20,21 In particular, experiments carried out using murine FAK ¡/¡ cells showed that FAK mediates haptotaxis elicited by the activation of a5b1 integrin, that binds a number of substrates including FN. 20 We therefore characterized the effects of FN on FAK activation in macrophages.…”
Section: Fn Induces Migration and Fak Activation In Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Moreover, later evidences definitively linked FAK to macrophage migration. 20,21 In particular, experiments carried out using murine FAK ¡/¡ cells showed that FAK mediates haptotaxis elicited by the activation of a5b1 integrin, that binds a number of substrates including FN. 20 We therefore characterized the effects of FN on FAK activation in macrophages.…”
Section: Fn Induces Migration and Fak Activation In Macrophagesmentioning
confidence: 99%
“…20,21 In particular, experiments carried out using murine FAK ¡/¡ cells showed that FAK mediates haptotaxis elicited by the activation of a5b1 integrin, that binds a number of substrates including FN. 20 We therefore characterized the effects of FN on FAK activation in macrophages. No previous data were indeed available on a possible link between FN-elicited signaling and FAK phosphorylation in macrophages.…”
Section: Fn Induces Migration and Fak Activation In Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45][46][47] Furthermore, in fibroblasts, neural cells or macrophages, migratory signals elicited by α4β1 are distinct from those elicited in the same cells by α5β1. [33][34][35][36] Their motility was dependent on α5/FAK signaling, but this was dispensable for α4β1-mediated signaling mediated through c-Src activation instead. In hematopoietic cells, integrin-dependent FAK signaling is thought to be important in integrating growth/survival signals, especially under stress.…”
Section: Integrin-dependent Signaling In Erythroid Cellsmentioning
confidence: 99%
“…33 For example, it has previously been shown that α5β1 and α4β1 integrins stimulate motility in fibroblasts, neural cells or macrophages through distinct mechanisms: an FAK/Pyk2 linkage is essential for α5-signaling, but not for α4-dependent signaling, which depends only on c-Src activation, 34,35 and paxillin can promote α4-mediated macrophage chemotaxis independently of FAK. 36 Consequently, it could be suggested that, for erythroid proliferative expansion in spleen, as occurs in α4 −/− mice, the α4/c-Src-dependent signaling is dispensable. If instead the α5/FAK-dependent signaling is responsible, then inhibition of this signaling should phenocopy the response of β1 D/D mice to stress.…”
Section: α4 Versus α5 Integrins Likely Elicit Different Signaling Resmentioning
confidence: 99%